2004
DOI: 10.3758/bf03196837
|View full text |Cite
|
Sign up to set email alerts
|

Tactile selective attention and body posture: Assessing the multisensory contributions of vision and proprioception

Abstract: This study addressed the role of proprioceptive and visual cues to body posture during the deployment of tactile spatial attention. Participants made speeded elevation judgments (up vs. down) to vibrotactile targets presented to the finger or thumb of either hand, while attempting to ignore vibrotactile distractors presented to the opposite hand. The first two experiments established the validity of this paradigm and showed that congruency effects were stronger when the target hand was uncertain (Experiment 1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
103
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(114 citation statements)
references
References 67 publications
(127 reference statements)
10
103
0
Order By: Relevance
“…Moreover, a single weight parameter for each reference frame was sufficient to account for uncrossed and for crossed performance, indicating that the integration follows the same principles in both postures. Effects of body posture on touch processing have often been attributed to the external reference frame of touch (Driver & Spence, 1998;Aglioti et al, 1999;Kennett et al, 2001;Yamamoto & Kitazawa, 2001a;Shore et al, 2002;Soto-Faraco et al, 2004;Röder et al, 2004;Eimer et al, 2004;Bolognini & Maravita, 2007;Azañón & Soto-Faraco, 2008;Heed et al, 2012;Buchholz et al, 2011;. This is because body posture determines the location of the stimulated skin region in space, but should not influence the processing of any other tactile stimulus characteristics .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a single weight parameter for each reference frame was sufficient to account for uncrossed and for crossed performance, indicating that the integration follows the same principles in both postures. Effects of body posture on touch processing have often been attributed to the external reference frame of touch (Driver & Spence, 1998;Aglioti et al, 1999;Kennett et al, 2001;Yamamoto & Kitazawa, 2001a;Shore et al, 2002;Soto-Faraco et al, 2004;Röder et al, 2004;Eimer et al, 2004;Bolognini & Maravita, 2007;Azañón & Soto-Faraco, 2008;Heed et al, 2012;Buchholz et al, 2011;. This is because body posture determines the location of the stimulated skin region in space, but should not influence the processing of any other tactile stimulus characteristics .…”
Section: Discussionmentioning
confidence: 99%
“…Yet, to plan actions toward the object, its location must be transformed into another, posture-dependent reference frame (Pouget et al, 2002;Sober & Sabes, 2005). Any perceived tactile stimulus seems to be transformed into an external-spatial reference frame (Driver & Spence, 1998;Yamamoto & Kitazawa, 2001a;Shore et al, 2002;Spence et al, 2004;Soto-Faraco et al, 2004;Röder et al, 2004;Schicke & Röder, 2006;Heed & Azañón, 2014;Heed et al, 2015), even when such recoding is currently not required (Kitazawa, 2002;Azañón et al, 2010a). This process of coordinate transformation is addressed as tactile remapping (Driver & Spence, 1998) and has been associated with regions of the intraparietal sulcus in posterior parietal cortex (Azañón et al, 2010b;Bolognini & Maravita, 2007;Renzi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It therefore seems that, despite the adequacy of the body-centred frame of reference in the absence of visual orienting behavior, a visual framework is used spontaneously to coordinate manual orientation responses (cf. Kitazawa, 2002;Soto-Faraco et al, 2004, for consistent evidence that adult humans cannot help but refer to a more external, possibly visual, representation when making purely tactile discrimination responses). The influence of a visual spatial framework on 6.5-month-olds' manual responses strongly suggests that this age group perceives tactile sensations with respect to visual spatial coordinates.…”
Section: Spatial Remapping Of Visual Responses Across Change In Posturementioning
confidence: 99%
“…Detection performance has been shown to be affected by the separation of the target and the distractor on the skin surface (see, e.g., Craig, 1974;Uttal, 1960). Researchers have also shown that the similarity between the target and distractor stimuli can modulate tactile discrimination performance as well (see, e.g., Driver & Grossenbacher, 1996;Evans & Craig, 1991;Soto-Faraco, Ronald, & Spence, 2004). Target responses have tended to be faster and more accurate when distractors were identical to the target, as compared with those trials in which the targets and distractors differed.…”
Section: Tactile Selectionmentioning
confidence: 99%